Chikungunya in infants: a descriptive study in a district hospital - Sengottaiyan, Palanivel; Muthusamy, Ramaswami (International Journal of Contemporary Pediatrics, 2020)
Background: To define the clinical profile of Chikungunya in infants admitted at a District Hospital in South India. Methods: All infants admitted in Government District Headquarters Hospital, Namakkal from January 2019 to December 2019 with fever (defined as axillary temperature > 99.6 F) and any one of the following features; seizure, loose stools, peripheral cyanosis, skin manifestations or pedal edema in children less than one year with chikungunya IgM ELISA positive were included in this study. Details of disease from onset of illness till admission were noted. This was a descriptive observational study. Results: Fifty-six (46) infants were included in this study, out of it 27(58.69%) were males and 19(41.30%) were females. 7(15.21%) infants were less than 1 month of age, 21(45.65%) were 2-6 months old and 18(39.13%) were 7-12 months old. Fever was invariably present but associated constitutional symptoms in infants consisted of lethargy or irritability and excessive cry. The most characteristic feature of the infection in infants was acrocyanosis and symmetrical erythematous rash were noted in most infants. Erythematous macules and patches were observed which later progressed to morbilliform rashes. Conclusions:Atypical clinical manifestations of chikungunya infection in infants as compared to older children to be carefully observed for its proper management. The morbidity and mortality of the disease may be avoided by the rational use of drugs and close monitoring of all infants.